Code Choice and Stance Taking by Two Mahragānāt Performers: A Case of Social Identity Construction in Egyptian Public Discourse - Abusamra, Yasmine (AUC Knowledge Fountain, 2022)
Mahragānāt [festivals] is a relatively new genre of Egyptian street music that broadly represents working-class values and culture. Performers are aware of their unprivileged origins and feature the concerns and interests of Egyptian slums in their songs. Their vocals are linguistically fixated on local urban realities of the working class and often express loyalty to singers’ neighborhoods. This qualitative study explores code choice in selected songs of two artists, Muhammad Ramadan and Ahmad Ali, and its relation to social class. Both performers overtly promulgate their unprivileged urban origin and employ their lyrics to reframe and negotiate their position in society through challenging the social distribution of power and the dominant language ideologies deeply rooted in Egyptian media. Further, the study seeks to know how the performers manipulate language to construct their social identity in the media and challenge the working-class stereotype. To that end, online and television interviews are analyzed to identify the two artists’ linguistic repertoire and their range of linguistic performance. The study adopts stance theory and indexicality as a theoretical framework for examining language form and content. A close qualitative examination of the mahragānāt sample, considering its spreading popularity among the Egyptian youth, demonstrates a possible undergoing change of language ideologies at large in Egyptian media as vernaculars gain more space, power, and prestige.